2018
DOI: 10.2136/sssaj2017.09.0327
|View full text |Cite
|
Sign up to set email alerts
|

Reliably Mapping Clay Content Coregionalized with Electrical Conductivity

Abstract: Core Ideas Surface clay content was derived through a combination of clay measurements and a proximal sensor. Apparent electrical conductivity (ECa) supported reliable clay content estimation. Predictions of clay coregionalized with ECa performed well, even for one soil sample per two hectares. Understanding the spatial variability of soil texture within field soils is important due to its influence on a large number of soil and plant related processes and for site‐specific application of inputs that are cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…]–corn ( Zea mays L.) rotation is practiced in the particular field of this study. Ten locations of soil samples across the field were selected by considering diverse conditions with regard to soil clay content based on the clay map in this field (Reyes et al, 2018). At each site, a soil pit was dug from the surface to the 1‐m depth (20‐cm depth increment, five depths).…”
Section: Methodsmentioning
confidence: 99%
“…]–corn ( Zea mays L.) rotation is practiced in the particular field of this study. Ten locations of soil samples across the field were selected by considering diverse conditions with regard to soil clay content based on the clay map in this field (Reyes et al, 2018). At each site, a soil pit was dug from the surface to the 1‐m depth (20‐cm depth increment, five depths).…”
Section: Methodsmentioning
confidence: 99%
“…For obtaining maps at a fine resolution in a reasonable computing time, all variables were interpolated in a 4-m-grid. For soil texture, a cokriging analysis was previously performed by combining soil clay content with EC as (Reyes et al, 2018). Detailed steps of kriging and cokriging procedures are explained in Nielsen and Wendroth (2003).…”
Section: Management Zone Delineationmentioning
confidence: 99%
“…The electrodes are configured with a Wenner array, and measurements that integrate EC over a shallow depth (~0-30 cm) and a deep depth (~0-90 cm) were obtained, defined as EC as and EC ad , respectively. More details about the EC a measurement are provided in Reyes et al (2018).…”
Section: Site Description and Data Samplingmentioning
confidence: 99%
“…The second challenge is to interpret that basic physical property in terms of some soil property of interest (see Table 1). For example, Reyes et al (2018) employed the geostatistical interpolation such as ordinary kriging and cokriging with the electrical conductivity data to identify the spatial variability of soil clay content at the field scale. A laboratory work by Gao et al (2013) demonstrated a relationship to calibrate the soil penetration resistance (i.e., soil strength) and the shear modulus (i.e., elastic property); their relationship was later adopted by Shin et al (2017) to predict the penetration resistance from the shear modulus deduced by acoustic to seismic method.…”
Section: Geophysical Properties Of Soilmentioning
confidence: 99%
“…The third method is an emerging method based on acoustic to seismic coupling. The first two methods have been used in agriculture and soil science for both mapping soil characteristics, such as salinity and clay content, and for more detailed studies of soil processes, often related to water and solute movement (Beff et al, 2013;Binley et al, 1996;Blanchy et al, 2020b;Dahlin et al, 2014;Koestel et al, 2008;Reyes, et al, 2018;Shanahan et al, 2015;. Methods based on the analysis of seismic waves are sensitive to the elastic properties of soil but also depend on soil water status and soil compaction.…”
Section: Introductionmentioning
confidence: 99%